Mixed crop-forage production system suitable for coastal subhumid Kenya - Mureithi, J.G. (International Livestock Centre for Africa, 1990)
Reports on a research project developed and currently being implemented in coastal Kenya whose broad objective is to determine whether a system of mixed crop and forage production can be developed in which output (food grain and feed production) can be sustained by using biologically fixed nitrogen, recycled nitrogen and management practices which maintain or improve soil physical characteristics and avoid erosion.